Oxfam: BlocRice project - Shahzad, Khuram (Henry Stewart Talks, 2024)
This case study of Oxfam’s BlocRice Project demonstrates the use of blockchain technology, particularly smart contracts, in improving the bargaining and negotiating power of small-scale rice farmers in Cambodia and digitally connecting supply chain participants.